2003
DOI: 10.1016/s0005-2728(03)00059-8
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear encoded subunits of complex I from bovine heart mitochondria

Abstract: NADH:ubiquinone oxidoreductase (complex I) from bovine heart mitochondria is a complicated, multi-subunit, membrane-bound assembly. Recently, the subunit compositions of complex I and three of its subcomplexes have been reevaluated comprehensively. The subunits were fractionated by three independent methods, each based on a different property of the subunits. Forty-six different subunits, with a combined molecular mass of 980 kDa, were identified. The three subcomplexes, I alpha, I beta and I lambda, correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
400
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(415 citation statements)
references
References 119 publications
13
400
2
Order By: Relevance
“…Complex I is the largest complex in the MRC containing at least 46 subunits. 20,21 It has been shown previously that IFN-b/RA treatment increases the mRNA level of GRIM-19 in human breast carcinoma cell lines. 10 In this study, we investigated whether IFN-b/RA treatment can also stimulate expression of other MRC subunits in these cancer cell lines.…”
Section: Resultsmentioning
confidence: 95%
“…Complex I is the largest complex in the MRC containing at least 46 subunits. 20,21 It has been shown previously that IFN-b/RA treatment increases the mRNA level of GRIM-19 in human breast carcinoma cell lines. 10 In this study, we investigated whether IFN-b/RA treatment can also stimulate expression of other MRC subunits in these cancer cell lines.…”
Section: Resultsmentioning
confidence: 95%
“…The caspase inhibitors z-VAD-fmk and DEVD-fmk have a partial effect, whereas the GB inhibitor Ac-IETD-CHO prevented NDUFV1 cleavage. Using CutDB and SitePrediction bioinformatics tool, 26,27 we found that GB has predicted cleavage sites for NDUFV1, NDUFS2, NDUFS1, NDUFS3, NDUFS7 and NDUFA13. Similar to NDUFV1, both NDUFS1 and NDUFS2 were cleaved in K562 cells treated with GB and P similarly to PARP-1 ( Figure 1f and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…al. has suggested that the 75 kDa subunit is associated structurally with the 51-and 24 kDa subunits of the Fp subcomplex based on the structural homology related to the α (51 and 24 kDa) and γ (75 kDa) subunits of the NAD-reducing hydrogenases and that the NuoE, F and G subunits of E. coli Complex I can be co-expressed to form a catalytically active recombinant subcomplex (1,34,35). The information of X-ray structure from T. thermophilius Complex I supports this prediction (32).…”
Section: Protein S -Glutathiolation In the 75 Kda Subunit Of Nqrmentioning
confidence: 99%